EFEKTIVITAS PENYELENGGARAAN TUGAS CAMAT DALAM IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH DI KECAMATAN TAHUNA KABUPATEN KEPULAUAN SANGIHE - BUDIMAN, RIRIN; Dengo, Salmin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : In accordance with the mandate of Law number thirty-two year two thousand and four and Government Regulation number nineteen year two thousand and eight, Head for the implementation of the regional autonomy policy has the task of carrying out public service administration in the district, and handles most affairs of autonomy bestowed by the regent or mayor and the authority of the government district with it, this study will answer the question: how effective maintenance tasks in the implementation of district Sub regional autonomy policy in Tahuna. Date This study uses Qualitative. Informant in this study consisted of fourteen people from the district government officials (four people), elements of leadership in the district or autonomous institution of the Department or Agency Unit (two people), management agency vertically (two people), Leader ( three people), and heads of organizations or public institutions (two men) .Instruments in this study is the researchers themselves, while primary data collection by interview. Date analysis is an analysis model of Miles and Hubernann Interactive. Based on these results at the district Sangihe Regency Tahuna can be deduced: (A) The effectiveness of the head maintenance tasks in the field of public service in general is good governance and effective, but there is still not maximized (B) Effectiveness district maintenance tasks in handling affairs of regional autonomy granted by the Regent on generally is good and effective, but there is still not maximized. Right on these conclusions, the recommended suggestions: (A) The coordination of the implementation of the common tasks of governance needs to be improved through regular coordination meetings every month with all the autonomous institutions and agencies existing vertical sub region, with the village government, and should also involve the leadership of the organization or public institutions at the district level; (B) Task district in handling affairs of regional autonomy granted by the regent should be clearly formulated in a District Regulation district as a reference in formulating programs and activities.